GE_GERICHTE C/2623/2009 vom 26. April 2013 - GE Cour de justice (2013)
OBLIGATION D'ENTRETIEN; MAXIME OFFICIELLE; UNITÉ DU JUGEMENT DE DIVORCE; COMPLÉMENT | LTF.93.1; LTF.93.3; CC.125; aLPC.94.2; aCC.280.2; CC.133.1; Cst.29.2; CPC.318.1.C.2; aCC.143; CC.285